Políticas públicas e diversidade na agricultura familiar: um estudo do Pronaf em Cachoeira do Sul/RS - Vargas, Daiane Loreto de (2012)
This article discusses the distinction that the National Program for Strengthening Family Farming (PRONAF) promotes among farmers in Cachoeira do Sul / RS, given that we are referring to a very heterogeneous social category, which includes over 80% of farms in Brazil. Which was built to provide the basis for public policy, created in the mid 90's and throughout its history has gone through many changes. Currently PRONAF operates in almost all municipalities in the country, have varying interest rates and financing agricultural credit in accordance with the guidelines of the different economic groups of farmers. But even acting in these conditions, the program has failed to meet the needs of the great heterogeneity of producers embraces the concept of family farming. Thus, this study aimed to: understand what are the differences between those farmers who access and those without access to PRONAF and the reasons for that decision, considered the characteristics of the plant and in the same socioeconomic study site. Thus, we performed a search in Cachoeira do Sul / RS, which was used for a qualitative and quantitative methodology, but with greater attention to qualitative aspects of research, since it had as its goal the understanding and quantification not numbers. We use the techniques of observation, semi-structured open interviews, a field diary, analysis of documents and photographs of the site. Where 35 farmers were interviewed in eleven locations within the municipality, 18 and 17 non-pronafianos pronafianos, and mediators of the organs (EMATER, STR, AF and Branch). The survey results indicate that PRONAF promotes a fairly sharp distinction between the farmers, non-pronafianos generally have lower incomes, live in smaller properties, make use of traditional technologies, have few social relationships and afraid to go into debt with bank branches. These differences are known mediators of the organs, but they eschew the situation and the distance between pronafianos and nonpronafianos in Cachoeira do Sul.